Does gender have a significant relationship with social courage? Test of dual sequentially mediated pathways. (1st June 2020) - Howard, Matt C.; Fox, Faith R.
Abstract: No widespread theoretical framework exists to study courage, and researchers must turn to lay theory to identify relationships that can develop more sophisticated theoretical integrations. We test the lay theory that men are more courageous than women. Three studies show that gender does not have a significant direct effect with an important dimension of courage, social courage; however, gender has dual sequentially mediated indirect effects with social courage that jointly produce an overall null effect. One indirect effect is through femininity and prosocial tendencies, whereas the other is through masculinity and risk taking. These results support that (a) the lay theory that men are more courageous than women is false– at least regarding social courage, (b) gender does have indirect relationships with social courage, (c) and contexts relevant to two central features of courage, prosocial tendencies and risk taking, may alter the social courage behaviors of feminine or masculine individuals.